A Scientific Framework for Managing Urban Natural Areas - Frank J. Mazzotti; Carol Morganstern (EDIS, 1996)
The purposes of this paper are: to present a scientific framework for managing urban natural areas; to discuss general ecological issues and management concerns identified from our early efforts at applying this approach to Broward County ESL sites; and to discuss the Pine Island Ridge ESL site as a case study.